Impact of port complex works on the coastal strip of Chancay Bay (Perú) - Bocanegra-García, Carlos A. (2021)
Objective. To describe the impacts of the preliminary works of what will be the megaport of Chancay (Peru), referred to the transformation of the coastal strip of the bay. Methods. The study had a qualitative approach and resorted to a combination of environmental history methodology and the use of photographs to visualize the changes that have occurred in the bay over time. Results. There was evidence of transformation in the configuration of the coastal area of the bay due to anthropic action, which can be summarized in the annulment of the bay's function that generated the alteration of the coastline, sedimentation processes and alteration of the coastal marine ecosystem. Conclusions. The bay of Chancay and its coastal strip have been transformed by the preliminary works of what will be a megaport. The transformation has meant the loss of the beach as a recreational space and habitat for important species that sustain the artisanal fishery. What was once a beach where the energy of the waves, tides and currents was discharged, has now become a rigid system in the face of natural hydrodynamic processes that has broken the natural balance of the system.